GPU accelerated Monte Carlo simulation of light propagation in inhomogeneous fluorescent turbid media: Application to whole field CW imaging - Carbone, Nicolás Abel (2017)
We present an implementation of a Monte Carlo simulation software for fluorescent turbid media, accelerated by aGPU (graphic processing unit). The code is based on previous work by Alerstam et al (2008 J. Biomed. Opt. 13 060504) and Wang et al (1995 Comput. Methods Programs Biomed. 47 131-46), with the addition of a voxelized medium without symmetries and with an inhomogeneous distribution of absorbers and fluorescent markers. Cartesian coordinates are used in place of the cylindrical ones used in previous versions. It is particularly aimed at the simulation ofCWwhole-field reflectance and transmittance images of fluorescence and absorption. Several tests and comparisons with numerical and theoretical techniques were performed in order to validate our approach.